Regulation of Apoptosis in African Swine Fever Virus–Infected Macrophages - Laslo Zsak; John G. Neilan (The Scientific World Journal)
A number of viruses have evolved antiapoptotic mechanisms to promote infected-cell survival, either to ensure efficient productive viral replication or to promote long-term survival of virus-infected cells. Recent studies identified critical African swine fever virus genes involved in the complex regulation of ASFV-host interactions. Here we review the present knowledge of the recently identified ASFV genes with special attention to those which affect viral virulence, host range, and pathogenesis by regulating viral-induced apoptotic mechanisms.